2015
DOI: 10.1016/j.copsyc.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Current directions in stress and human immune function

Abstract: Psychological stress has been linked empirically with dysregulation of facets of the human immune system, yet these effects are not the same in every situation or population. Recent research has made strides towards understanding risk factors for immune dysregulation as well as why these risks occur. This review discusses mechanisms and mediators underlying the stress-immune relation, the role of context in determining whether an immunologic responses to stress is adaptive versus maladaptive, and the stress-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
169
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(197 citation statements)
references
References 45 publications
4
169
0
4
Order By: Relevance
“…For instance, an epidemic can overload a nation's healthcare system, especially in poor public health contexts (Bloom and Cadarette 2019), limiting the ability of operators to deal with the problem and increasing the stress levels of both citizens and healthcare workers. In turn, stress has been previously shown to worsen both the physical and mental health of individuals, often resulting in increased use of alcohol, tobacco, or other drugs (Centers for Disease Control and Prevention 2020c) and negatively affecting the immune system, making people more vulnerable to disease (e.g., Morey et al 2015). Moreover, fear experienced during an epidemics has been previously associated with the stigmatization of citizens perceived as being the source of the disease, with the risk of resulting in scuffles or, in extreme cases, civil conflicts (Pappas et al 2009;Falagas and Kiriaze 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an epidemic can overload a nation's healthcare system, especially in poor public health contexts (Bloom and Cadarette 2019), limiting the ability of operators to deal with the problem and increasing the stress levels of both citizens and healthcare workers. In turn, stress has been previously shown to worsen both the physical and mental health of individuals, often resulting in increased use of alcohol, tobacco, or other drugs (Centers for Disease Control and Prevention 2020c) and negatively affecting the immune system, making people more vulnerable to disease (e.g., Morey et al 2015). Moreover, fear experienced during an epidemics has been previously associated with the stigmatization of citizens perceived as being the source of the disease, with the risk of resulting in scuffles or, in extreme cases, civil conflicts (Pappas et al 2009;Falagas and Kiriaze 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that short-term stress can activate the hypothalamic-pituitaryadrenal axis, leading to redistribution of leukocytes to tissues. [13][14][15][16][17][18] Chronic stress can eventually lead to attenuated immune response over time. 13,16,[18][19][20] Hypothalamic-pituitary-adrenal axisimmune system coordination may be mediated by release of the stress hormone cortisol, which can be measured in saliva.…”
mentioning
confidence: 99%
“…Less clear are the effects of long-term stress on immunity. Chronic stress seems to have both pro and antiinflammatory components, with chronically increased levels of proinflammatory cytokines, a blunted response to cortisol and impaired cellular and anti-viral immunity [2]. Since the overall effects of chronic stress on the immune system appear to be rather detrimental, it is usually interpreted as maladaptive [65 ].…”
Section: Box 1 Violations Of Well-being: Stress and Depressionmentioning
confidence: 99%
“…The effects of stress and depression on basal immune functioning are extensively reviewed elsewhere and are not the focus of this review (for more information on depression see [1,4,64]; for stress we recommend [2,65 ]). However, since we consider depression, acute stress, and chronic stress the most important pathological, physiological, and mal-adaptive violations of well-being, respectively, we decided to mention them here shortly.…”
Section: Box 1 Violations Of Well-being: Stress and Depressionmentioning
confidence: 99%